Calamitic-rod-shaped mesogens based on chalcone esters comprising varying alkoxy and lauryl ester chains: Synthesis, mesomorphism and computational study. (13th October 2017) - Sharma, Vinay S.; Patel, Sunil B.; Sharma, Anuj S.; Patel, R. B.
GRAPHICAL ABSTRACT: ABSTRACT: In this study we have synthesized a new class of compounds incorporating of chalconyl-ester and terminally substituted lauryl group. A series of new chalcones with three aromatic rings is synthesized and characterised by elemental analyses and spectroscopic techniques such as Fourier transform infrared [FT-IR] and proton magnetic resonance magnetic resonance [ 1 H NMR] spectroscopy. The mesomorphic properties of these compounds were observed by optical polarized light microscopy (POM) and confirmed by differential scanning calorimetry (DSC). It is found that all the prepared materials display enantiotropic LCs phases except first two homologue in present series. The lower member comp. (C3 to C6 ) display only SmC phase while comp. (C7 to C12 ) shows smectic C as well as nematic phase. The higher member comp. (C14 to C18 ) display only nematic phase in heating and cooling condition. To get more insights, the HOMO, LUMO studies are carried out which supports intramolecular charge transfer interactions in this class of mesogens.